Using artificial intelligence to determine the influence of dental aesthetics on facial attractiveness in comparison to other facial modifications. (9th May 2022) - Obwegeser, Dorothea; Timofte, Radu; Mayer, Christoph; Eliades, Theodore; Bornstein, Michael M; Schätzle, Marc A; Patcas, Raphael
Abstract: Background: Facial aesthetics is a major motivating factor for undergoing orthodontic treatment. Objectives: To ascertain—by means of artificial intelligence (AI)—the influence of dental alignment on facial attractiveness and perceived age, compared to other modifications such as wearing glasses, earrings, or lipstick. Material and methods: Forty volunteering females (mean age: 24.5) with near perfectly aligned upper front teeth [Aesthetic Component scale of the Index of Orthodontic Treatment Need (AC-IOTN) = 1 and Peer Assessment Rating Index (PAR Index) = 0 or 1] were photographed with a standardized pose while smiling, in the following settings (number of photographs = 960): without modifications, wearing eyeglasses, earrings, or lipstick. These pictures were taken with natural aligned dentition and with an individually manufactured crooked teeth mock-up (AC-IOTN = 8) to create the illusion of misaligned teeth. Images were assessed for attractiveness and perceived age, using AI, consisting of a face detector and deep convolutional neural networks trained on dedicated datasets for attractiveness and age prediction. Each image received an attractiveness score from 0 to 100 and one value for an age prediction. The scores were descriptively reviewed for each setting, and the facial modifications were tested statistically whether they affected the attractiveness score. The relationship between predicted age and attractiveness scores was examined with linear regression models. Results: All modifications showed a significant effect (for all: P < 0.001) on facial attractiveness. In faces with misaligned teeth, wearing eyeglasses (−17.8%) and earrings (−3.2%) had an adverse effect on facial aesthetics. Tooth alignment (+6.9%) and wearing lipstick (+7.9%) increased attractiveness. There was no relevant effect of any assessed modifications or tooth alignment on perceived age (all: <1.5 years). Mean attractiveness score declined with predicted age, except when wearing glasses, in which case attractiveness was rated higher with increasing predicted age. Conclusions: Alignment of teeth improves facial attractiveness to a similar extent than wearing lipstick, but has no discernable effect on perceived age. Wearing glasses reduces attractiveness considerably, but this effect vanishes with age.